RADIOCARBON CHRONOLOGY OF SETTLEMENTS OF BII AND CI STAGES OF THE TRIPOLYE CULTURE AT THE MIDDLE DNIEPER - Videiko, Mihailo Y. (Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Prahistorii, Uniwersytet im. Adama Mickiewicza (Poznań). Instytut Wschodni, 2003)
This volume of the Baltic-Pontic Studies is a record of investigations carried out under the research project begun earlier in vol. 7 ("The Foundations of radiocarbon chronology of cultures between the Vistula and Dnieper: 3150-1850 BC", Poznań 1999). Here, the approach is broader in terms of chronology and culture. Our purpose has been to fill taxonomic gaps hitherto present in the discussion (supplementing the dating of cultures, groups or phases) or reanalyze the grounds for findings considered particularly controversial. In the latter case, a very enlightening debate was provoked by the comparative chronology of the Yamnaya and Catacomb cultures presented by A.N. Nikolova. We hope that a large series of 14C dates and a revision of the foundations of "archaeological knowledge" (stratigraphy, typochronolgy and groups of co-occurrence of traits), brought together in the paper by D.Y. Telegin, S.Z. Pustovalov, N. Kovalyukh, lay the ground for a stabilization of views on this important dividing line in the chronology of the Bronze Age in the Pontic zone. A vast majority of the new 14C dates have been obtained under an international research project financed by the Polish Committee for Scientific Research.